Proposta de melhoria do processo de aquisição de material e contratação de serviços na administração pública - modelo aplicável à marinha de guerra - Rodrigues, Marcos Figueiredo (2000)
The aim of this study with the current legislation on acquitions for the Public Administration, that was a contrast and adaptation of modern techniques in use in tbe marketing, especiaIly with the implementation of the top technology of information, was to propose the application of a model to speed up the system of materials acquisitions and service hirings within the suppliers and the Brazilian Navy, based on the current Licitation Laws. It implicates on the improvement of the acquisition process for tbe wbole Public Service that relies on the same legislations.